2021
DOI: 10.1111/1365-2664.13962
|View full text |Cite
|
Sign up to set email alerts
|

Flowers as dirty doorknobs: Deformed wing virus transmitted between Apis mellifera and Bombus impatiens through shared flowers

Abstract: In light of bee declines, the importance of pollination services from managed and native bees to our agriculture and economy is of great political, scientific and public interest. Viruses, first observed in honeybees, have been documented in bumblebees and the prevalence and load of some RNA viruses have been associated with managed honeybees. Shared flowers may be the bridge across which viruses pass between bees but no study has yet demonstrated that bumblebees can pick up viruses while foraging on contamina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 47 publications
(78 reference statements)
3
40
0
Order By: Relevance
“…Although both the AKI-virus complex and SBPV can also be vectored and amplified to lethal levels in honey bee colonies by V. destructor , these viruses are more commonly found in wild bees 20 , 59 , 61 , 68 , 69 , suggesting key differences in host susceptibility and competence between these three viruses. The strong relations found in our study between viral prevalence in honey bees and wild bees together with the results from previous studies 19 , 55 highlight the need for good beekeeping practices, which include proactive varroa monitoring and control by beekeepers as well as appropriate hive placement, where the beekeeper takes into account the presence of endangered wild bees, to prevent managed honey bee colonies becoming sources of virus amplification and dissemination to wild bees 19 , 55 , 70 .…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Although both the AKI-virus complex and SBPV can also be vectored and amplified to lethal levels in honey bee colonies by V. destructor , these viruses are more commonly found in wild bees 20 , 59 , 61 , 68 , 69 , suggesting key differences in host susceptibility and competence between these three viruses. The strong relations found in our study between viral prevalence in honey bees and wild bees together with the results from previous studies 19 , 55 highlight the need for good beekeeping practices, which include proactive varroa monitoring and control by beekeepers as well as appropriate hive placement, where the beekeeper takes into account the presence of endangered wild bees, to prevent managed honey bee colonies becoming sources of virus amplification and dissemination to wild bees 19 , 55 , 70 .…”
Section: Discussionsupporting
confidence: 74%
“…Interestingly, the effects of managed honey bee viral prevalence on wild bee viral prevalence did not differ between bumble bees and solitary bees, despite their different lifestyles and social organization, thereby underlining the importance of interspecific pathogen transmission, e.g. via shared floral resources 16 , 39 , 42 , 54 , 55 . Even though some solitary bee species are dietary specialists, visiting flowers of only a few plant species, the presence of generalist species such as honey bees connect many species in one network module, increasing the likelihood of viral transmission to all bee species present in the same environment 56 60 .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, in laboratory assays with genetically labelled DWV, Gusachenko et al [26] were able to demonstrate that DWV actively replicates when injected into the Western Palearctic Bombus terrestris (see also [27]) but failed to demonstrate viral acquisition and replication by feeding, questioning the spillover of DWV from honeybees to bumblebees through shared resource use at flowers in the field. In a more recent series of flight cage experiments with B. impatiens and DWV, Burnham et al [28] have now demonstrated the potential for viral transmission from honeybees to bumblebees as well as transmission from Bombus back to Apis; DWV-infected honeybees deposited DWV onto red clover (Trifolium pratense), B. impatiens foraging on DWV-infected flowers became infected with DWV, and DWV-infected B. impatiens themselves deposited DWV onto artificial flowers in a laboratory setting. It is unclear whether differences among studies in the potential for transmission of DWV (from Apis to Bombus) reflect the choice of Bombus species or experimental paradigm.…”
Section: Introductionmentioning
confidence: 99%